Determinants of Financial Reporting Timeliness: A Study of Indonesian Consumer Cyclicals Companies - Inawati, Wahdan Arum; Azizah, Adinda Noor (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to examines the influence of adoption of extensible business reporting language (XBRL) and corporate governance (CG) on financial reporting timeliness. CG variables consist of size of the board of directors, institutional ownership, and auditor turnover by involving corporate size and audit opinion as control variables. The samples of this study are 87 companies of consumer cyclicals sector listed in the Indonesian Stock Exchange between 2019 and 2021 consistently (or 261 observations). Data were analyzed using the logistic regression method and the results show that institutional ownership, and auditor turnover have a significant influence, while XBRL adoption and board size do not have a significant influence on timeliness of financial reporting in the sample companies. Institutional ownership has a positive influence, while auditor turnover has a negative influence on timeliness of financial reporting.